2009
DOI: 10.1007/128_2008_40
|View full text |Cite
|
Sign up to set email alerts
|

An Orbital Phase Theory

Abstract: Cyclic orbital interactions are contained in non-cyclic conjugation as well as cyclic conjugation. For effective interactions, the orbitals are required to meet simultaneously the phase continuity conditions: (1) out of phase relation between electron-donating orbitals; (2) in phase relation between electron-accepting orbitals and between electron-donating and -accepting orbitals. The orbital phase theory is applicable to diverse chemical phenomena of non-cyclic conjugate systems, e.g., relative stabilities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 134 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…To elucidate the origin of the effect of N -methylation on Z / E thioamide preference (Table ), we analyzed the electronic structures of the molecules in terms of the orbital interactions of thioacetamides ( 1a/3a and 1 b /3b ) by means of bond model analysis (BMA) (Tables S2–S4). , The interbond energies (IBEs), including both occupied-occupied orbitals and occupied-vacant orbitals, were used to evaluate the bond interactions in the molecules. The IBEs were calculated for (1) vicinal bond interactions with respect to the thioamide N–C­(S) bond, that is, between σ­(C1–C2)/σ­(C1–S) and σ­(N–H)/σ­(N–C­(Ar)) (they are in a vicinal relation; see Figure ), (2) conjugation between n (N) and CS, n (N) and Ar, and CS and Ar, and (3) repulsive interaction between two substituents attached to the thioamide bond, including all C–C and C–H σ bonds and π orbitals of the aromatic ring.…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the origin of the effect of N -methylation on Z / E thioamide preference (Table ), we analyzed the electronic structures of the molecules in terms of the orbital interactions of thioacetamides ( 1a/3a and 1 b /3b ) by means of bond model analysis (BMA) (Tables S2–S4). , The interbond energies (IBEs), including both occupied-occupied orbitals and occupied-vacant orbitals, were used to evaluate the bond interactions in the molecules. The IBEs were calculated for (1) vicinal bond interactions with respect to the thioamide N–C­(S) bond, that is, between σ­(C1–C2)/σ­(C1–S) and σ­(N–H)/σ­(N–C­(Ar)) (they are in a vicinal relation; see Figure ), (2) conjugation between n (N) and CS, n (N) and Ar, and CS and Ar, and (3) repulsive interaction between two substituents attached to the thioamide bond, including all C–C and C–H σ bonds and π orbitals of the aromatic ring.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on analysis of N -acetyl pyrazole 2 and N -2′,4′,6′-trichlorobenzoyl pyrazole 6b to determine the origin of the E -conformer preference. The electronic structures of the molecules were analyzed using bond model analysis, which is able to evaluate the bond orbital interactions in molecules …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that the phase of the orbitals 1 , which originates from the wave character of electrons in molecules, plays an essential role in determining reactivity and selectivity. Especially, cyclic orbital interaction 2 , in which a series of orbitals interact in a monocyclic manner, determines the regioselectivity in deprotonation of an indole sidechain 3,4 , diastereoselectivity in pericyclic reactions 5 including the electrocyclic ringopening reaction of 3-substituted cyclobutenes 6,7 , cheletropic reactions 8 and the retro-Nazarov reaction. 9,10 Recently, we reported that diastereoselectivity in the uncatalyzed Mukaiyama aldol reaction 11 and the electrophilic addition of -substituted ethylenes 12 are under the control of cyclic orbital interaction.…”
mentioning
confidence: 99%